Lukun Villagers’ Local Wisdom on Managing Fire Disaster Impact in Kepulauan Meranti Regency of Riau Province - Ashaluddin Jalil, Andri Sulistyani (International Journal of Advanced Science and Technology, 2020)
Lukun Village is one of many villages located in Tebing Tinggi District, KepulauanMeranti Regency, Riau Province. This village is a peat area with a high vulnerability of land fire disaster. In the past 5 years, the peatland of this village has experienced 3 times of land fires with variations ofthe affected area and material losses. The haze has also even reached Malaysia and Singapore. This article tends to discuss the local wisdom of Lukun villagers to survive and maintain the effects of land fires and also the continuity of their natural ecosystems. The data was taken by in-depth interviews and observations. The results show that the Lukun villagers have their local wisdom on managing the fire land in form of a traditional farming method with land clearing system regulated by local custom (adat), planting sago as a united (bersebati) plant of peatland, making trenches and small water reservoir (embung) as preparation in extinguishing the fire land and managing the sago stems mobility, and doing mutual cooperation in treating the trenches. Their traditional leadership holds by datuk, who plays important roles in all aspects of villagers’ life. This indigenous community structure has proven to facilitatecoordination in handling the impact of land fire disasters. Keywords:local wisdom, peat-lands, fire disaster impact management.